Separation of motions and vibrational separation of fractions for biocide brass - Mirna Sabbouh; Anna Nikitina; Elizaveta Rogacheva; Lyudmila Kraeva; Sviatlana A. Ulasevich; Ekaterina V. Skorb; Michael Nosonovsky (Ultrasonics Sonochemistry, 2021)
The mathematical method of separation of motions represents the effect of fast high-frequency oscillations by an effective averaged force or potential. Ultrasound acoustic vibrations are an example of such rapid oscillations leading to cavitation in water due to the gas phase formation (bubbles). Ultrasound cavitation is used to treat the surface of brass microparticles submerged in water. The formation of bubbles and their collapse triggers the modification of surface roughness and chemical composition. Consequently, the suspension separates into various fractions related to demonstrating biocide properties. While the exact mechanism of this process is complex, it can be explained phenomenologically by using the Onsager reciprocal relations for coupling the copper ion diffusion with the gas phase separation in water as a result of the action of the effective average vibrational force.